Medial fibular transport with the Ilizarov apparatus in the treatment of infected tibial pseudarthrosis - Maksim Kovačević; Marijana Kovačević; Verica Prodanović; Sanja Marić; Nada Avram; Aleksandar Tanović; Dražan Erić (Биомедицинска истраживања, 2024)
Introduction: Tibial bone defects, particularly those caused by infections, represent one of the most complex challenges in orthopedics. Given the severity of complications such as limb function loss or even amputation, the need for innovative and reliable treatment methods is crucial. Medial fibular transport using the Ilizarov apparatus offers a successful solution to these problems, preserving limb functionality and integrity. Case report. This paper presents the case of a 76-year-old patient with chronic osteomyelitis and infected tibial pseudarthrosis. Following radical debridement and sequestrum removal, a significant partial bone defect measuring 8 cm remained. Treatment was performed using medial fibular transport with the Ilizarov apparatus. The reconstruction process lasted eight months, after which complete bone consolidation, infection elimination, and restoration of limb function were achieved. Conclusion: The medial fibular transport technique has proven to be an effective and safe method for treating large tibial defects associated with infection, enabling limb preservation and significantly improving patients’ quality of life.
Keywords: fibular transport; Ilizarov; pseudarthrosis; osteomyelitis